Pembelajaran Nahwu Dengan Menggunakan Kitab Al- Fushul Al- Fikriyah Karya Syeikh Abdullah Basya Fikri : Learning Nahwu Using The Book Of Al-Fushul Al-Fikriyah By Syeikh Abdullah Basya Fikri - Ni’am, Mohammad Shulkhi; Rifa’I, Ahmad; Humaidi, Anis (Al-Wasil, 2023)
This study aims to determine a series of processes and results in implementing nahwu learning in class 4 Ibtida' Al-Amien Islamic Boarding School, Kediri City using the book al-fushul al-fikriyah. The approach used in this study is a qualitative descriptive research type, and the data analysis used in this study is the Miles and Huberman version of the analytical model. In collecting data, researchers used observation, interviews, and documentation related to learning the book al-fusul al-fikriyah at the cottage. The results of the research show that the learning begins with a lesson plan that is prepared and prepared by the ustadz and the students so that learning runs more effectively. Furthermore, the implementation of learning through the deductive method is accompanied by several supporting activities such as reasoning, deliberation, rote deposition, practice reading and analyzing pronunciation in books. Evaluation of learning consists of oral tests, written tests and assignments. The learning outcomes can be said to be effective and optimal. This is evidenced by the acquisition of students' scores that reach even more than the average value that has been determined, and an increase in students' understanding and mastery of nahwu science after studying the book.